Peran Brand Trust dan Brand Reputation dalam Menguatkan Pengaruh Brand Awareness terhadap Brand Performance Kasus pada Langit Musik - Teguh Widodo; Dheana Rakhmawati (IPB University, 2021)
This study aims to analyze the factors that affect the brand performance of Langit Musik service with brand awareness as an exogenous variable. Brand awareness is hypothesized to affect brand performance either directly or indirectly. The entire hypothesis proposed forms a research framework in the structural equations (SEM) model. Empirical data was obtained through an online survey of 238 respondents who answered 24 questionnaire questions in full. The selection of respondents was determined by a non-probability sampling approach from users who have used and are using Langit Musik service in Indonesia. The software used to perform a series of statistical tests informs that all indicators used meet the criteria of validity and reliability, the research model meets the match criteria, the seven hypotheses submitted, the whole is accepted based on the t-significance test, and produces strong factors. The three variables and their expansion have a positive and significant effect on brand performance. The biggest influence of variables on consecutive brand performance is brand awareness, brand reputation, brand trust. To improve performance, Langit Musik can increase its promotion so that people can get to know langit musik service. The next study is expected to expand the variables one of which is purchase decisions placed after the brand performance variable in order to improve the hypothesis of the model.